2008
DOI: 10.1093/toxsci/kfn040
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Putative Biomarkers of Nephrotoxicity after Exposure to Ochratoxin A In Vivo and In Vitro

Abstract: The kidney is one of the main targets of xenobiotic-induced toxicity, but early detection of renal damage is difficult. Recently, several novel biomarkers of nephrotoxicity have been identified by transcription profiling, including kidney injury molecule-1 (Kim-1), lipocalin-2, tissue inhibitor of metalloproteinases-1 (Timp-1), clusterin, osteopontin (OPN), and vimentin, and suggested as sensitive endpoints for acute kidney injury in vivo. However, it is not known if these cellular marker molecules may also be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
72
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(89 citation statements)
references
References 48 publications
15
72
2
Order By: Relevance
“…These measurements are often regarded as reliable markers of kidney damage [31] and indicate the loss of a majority of kidney function [32]. These elevated assessments are in agreement with the studies of Hashmi et al [33], who reported increased serum levels of creatinine and urea in albino rabbits following administration of antituberculosis drugs.…”
Section: Discussionsupporting
confidence: 88%
“…These measurements are often regarded as reliable markers of kidney damage [31] and indicate the loss of a majority of kidney function [32]. These elevated assessments are in agreement with the studies of Hashmi et al [33], who reported increased serum levels of creatinine and urea in albino rabbits following administration of antituberculosis drugs.…”
Section: Discussionsupporting
confidence: 88%
“…58 The occurrence of albuminuria has been shown to precede the increase of urinary NAG and serum creatinine. 59 A drawback of urine albumin, as marker of AKI, is its presence also in chronic renal failure.…”
Section: Microalbuminmentioning
confidence: 99%
“…58 Such toxicity is partly due to the high renal blood flow rate, which leads to delivery of high concentrations of xenobiotics to the kidneys. 59 Regarding kidney functions, serum urea and creatinine, the traditional kidney function tests, were assessed. Both blank and PIP-loaded cubs formulations treated groups showed no nephrotoxic effect indicating safety of the prepared formulations ( Table 7).…”
Section: Biochemical Testsmentioning
confidence: 99%